Male‐Female Supply to State Government Jobs and Comparable Worth - Orazem, Peter F.; Mattila, J. Peter (Journal of Labor Economics, 1998)
The proportion of women in state government jobs and applicant pools is well explained by a model emphasizing supply‐side factors. Relative to men, women's supply is least sensitive to wages in predominantly male jobs and most sensitive to wages in predominantly female jobs. These results suggest that comparable worth policies that shift relative pay toward traditionally female jobs and away from traditionally male jobs will increase the proportion of females in male‐dominated, female‐dominated, and total state government jobs. The implication is that supply side responses need not prevent comparable worth pay adjustments from raising total female compensation.